Nonideality of volume flows and phase transitions of F-actin solutions in response to osmotic stress. - Ito, T (1987)
Ovalbumin and G-actin solutions decreased their volume in a concentration-dependent manner in response to an osmotic stress, arising from an osmotic pressure gradient of 5-20 cm H2O at 25 degrees C, at protein concentrations as high as 20 mg/ml. In contrast, solutions of F-actin exhibited a concentration-dependent decrease in their rate of volume change in response to the osmotic stress. Shortening of F-actin by gelsolin did not affect this decrease, suggesting that the elastic response of the filaments underlies the osmotically nonideal behavior. However, above a critical actin concentration of approximately 7 mg/ml, no volume change occurred in response to osmotic gradients as high as 20 cm H2O. The concentration at which this critical phenomenon occurred and its abolition by shortening of F-actin by gelsolin suggest that a transition of diffusible rods to a glassy state is the cause of this critical phenomenon. Above the critical concentration, an increase in the osmotic pressure applied to an F-actin solution to greater than 20 cm H2O produced a transient increase in flow rate to that expected for a solution containing no polymer. This finding may represent a transition from an isotropic glassy state to an anisotropic and heterogeneous one wherein regions of pure solvent coexist with domains of pure polymer.